Strategi Peningkatan Kompetensi Pengarah Acara TVRI Jawa Barat Sesuai SKKNI - Yuni Wulandari; Ade Wahyudin (Institut Seni Indonesia Yogyakarta, 2020)
Strategy for Improving the Competency of Program Directors of TVRI in West Java Complying with SKKNI. A television program production is a complex creative process and it requires a good teamwork. Therefore, it needs a competent program director having the skill in broadcasting and leadership in directing a television program. An effective development of human resources is also needed to enhance the competency and professionalism of a television program director. Based on an interview and an observation at TVRI station in West Java, a fact was found that none of the television program directors has a SKKNI certificate, even though they have mastered the skill and have been knowledgeable. This is due to the lack of encouragement from the policy makers at TVRI station to improve the human resource's competency with a professional certificate. With a SKKNI certification, a television program director can show his competence related to the profession and is valid for a lifetime. Therefore, using the SWOT approach, it can be concluded that there is a need for a socialization regarding the importance of the SKKNI professional certification for TVRI Station in West Java that will promote the development of the competency for television program directors. It will surely need a great support from the television station itself. In addition, a cooperation of the Professional Certification Institution with the television and multimedia industries is highly needed, so that the television program directors are able to produce high quality television programs. ABSTRAKSebuah produksi program acara televisi merupakan hasil proses kreatif yang rumit dan memerlukan kerja sama tim yang baik. Untuk itu, diperlukan seorang pengarah acara yang memiliki kompentensi dalam hal kemampuan skill penyiaran dan kepemimpinan dalam mengatur jalannya sebuah program acara televisi. Pengembangan SDM yang efektif juga dibutuhkan untuk meningkatkan kompetensi dan profesionalisme pengarah acara televisi. Berdasarkan wawancara dan observasi di Stasiun TVRI Jawa Barat didapatkan suatu fakta bahwa tidak ada seorang pun pengarah acara televisi yang memiliki sertifikasi profesi SKKNI pengarah televisi, walaupun secara pengetahuan dan kemampuan sudah mumpuni. Hal ini dikarenakan kurangnya dorongan dari pemangku kebijakan di Stasiun TVRI untuk meningkatkan kompetensi SDM melalui sertifikasi profesi. Dengan sertifikasi SKKNI, seorang pengarah acara dapat menunjukkan kompetensi yang berkaitan dengan profesi dan berlaku seumur hidup. Hasil analisis menggunakan pendekatan SWOT menghasilkan kesimpulan bahwa perlu adanya sosialisasi yang mendalam mengenai pentingnya sertifikasi profesi SKKNI di Stasiun TVRI Jawa Barat yang mendorong pengembangan kompetensi pengarah acara televisi. Hal ini perlu dukungan dari pihak stasiun televisi. Selain itu, perlu ditingkatkan kerja sama Lembaga Sertifikasi Profesi dengan industri televisi dan multimedia sehingga seorang pengarah acara televisi mampu menghasilkan karya program acara televisi yang baik dan berkualitas.